2021
DOI: 10.21203/rs.3.rs-141873/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome and Metabolomic Analysis to Reveal the Browning Spot Formation of ‘Huangguan’ Pear

Abstract: Background: Browning spot (BS) disorders seriously affect the appearance quality of ‘Huangguan’ pear and cause economic losses. Many studies on BS have mainly focused on physiological and biochemical aspects, and the molecular mechanism is unclear.Result: In the present study, the structural characteristics of ‘Huangguan’ pear with BS were observed with SEM, the water loss and brown spot were evaluated, and transcriptome and metabonomics analyses were conducted to reveal the molecular mechanism of ‘Huangguan’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In studies of Arabidopsis thaliana, transcription of AtbZIP44 was responsive to temperature, and under ABA, salt and osmotic stress, transcription of AtbZIP53 was upregulated in seeds, and transcription of AtbZIP2 was downregulated in roots (Kang et al, 2002;Weltmeier et al, 2009). BS is reported to be associated with light irradiation, sudden drops in temperature, calcium deficiency, and various physiological, developmental and hormonal responses (Li et al, 2008;Wang et al, 2011;Wang et al, 2021). These results provide evidence of the potential involvement of bZIP genes in the formation of BS on the surface of 'Huangguan' pear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In studies of Arabidopsis thaliana, transcription of AtbZIP44 was responsive to temperature, and under ABA, salt and osmotic stress, transcription of AtbZIP53 was upregulated in seeds, and transcription of AtbZIP2 was downregulated in roots (Kang et al, 2002;Weltmeier et al, 2009). BS is reported to be associated with light irradiation, sudden drops in temperature, calcium deficiency, and various physiological, developmental and hormonal responses (Li et al, 2008;Wang et al, 2011;Wang et al, 2021). These results provide evidence of the potential involvement of bZIP genes in the formation of BS on the surface of 'Huangguan' pear.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a bioinformatics method was used for genome-wide identification of the bZIP gene family in white pear, and the gene structure, physicochemical properties, conserved motifs, phylogenetic relationships, chromosomal locations, collinearity and cis-acting elements of bZIP family members were analyzed. In our previous study, we found that gibberellin A 3 (GA 3 ) has a promoting effect on brown spot (BS) (Wang et al, 2021). In the present study, the expression levels of bZIP genes in exocarp of 'Huangguan' pear were evaluated in normal fruit, fruit with BS and fruit treated with GA 3 .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In pear fruit, stone cell growth relies in the biosynthesis of two types of lignin, namely, guaiacyl lignin (G-lignin) and syringyl lignin (S-lignin) [14,15]. For different pear varieties and developmental stages, structural genes were identified as hub genes involved in the lignin pathway [16][17][18][19][20], Table S1. Pears are rich in various lignin biosynthesis genes since the expansion of lignin synthesis gene family contributes to the large accumulation of lignin [21].…”
Section: Introductionmentioning
confidence: 99%